Histological, enzymatic and chemical analyses of the potential effects of differently sized microplastic particles upon long-term ingestion in zebrafish (Danio rerio). (April 2020) - Batel, Annika; Baumann, Lisa; Carteny, Camilla Catarci; Cormier, Bettie; Keiter, Steffen H.; Braunbeck, Thomas
Abstract: In microplastics (MPs) research, there is an urgent need to critically reconsider methodological approaches and results published, since public opinion and political decisions might be based on studies using debatable methods and reporting questionable results. For instance, recent studies claim that MPs induce intestinal damage and that relatively large MPs are transferred to, e.g., livers in fish. However, there is methodological criticism and considerable concern whether MP transfer to surrounding tissues is plausible. Likewise, there is an ongoing discussion in MP research if MPs act as vectors for adsorbed hazardous chemicals. In this study, effects of very small (4–6 μm) and very large (125–500 μm) benzo(a) pyrene (BaP)-spiked polyethylene (PE) particles administered via different uptake routes (food chain vs. direct uptake) were compared in a 21-day zebrafish ( Danio rerio ) feeding experiment. Particular care was taken to prevent cross-contamination of MPs during dissection and histological sample preparation. In contrast to numerous reports in literature describing similar approaches, independent of exposure route and MP size, no adverse effects could be detected. Likewise, no BaP accumulation could be documented, and MPs were exclusively seen in the lumen of the intestinal tract, which, however, did not induce any histopathological effects. Results indicate that in fish MPs are taken up, pass along the intestinal lumen and are excreted without any symptoms of adverse effects. Highlights: Good laboratory practices prevent cross contamination and misleading results, especially in histological analyses. There was no evidence of significant uptake into surrounding tissues, accumulation and translocation of MPs upon ingestion. There was no evidence of significant benzoa(a)pyrene (BaP) uptake in fish upon ingestion of spiked microplastics.